ANALISIS STRATEGI PADA USAHA KECIL MENENGAH (UKM) SEPATU DUCERY’S UD.SUMBER REJEKI JOMBANG - Kadek Yudha Agastya Tantra; Nurul Khusniyah Indrawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
In ordert to win the competition,business needs a strategy for to survival. This research aim to know the strategy by using environment analysis which implemented for UD.Ducery’s. The method used in this research is a descriptive. The data analysis used SWOT analysis and QSPM. The research results that UD.Ducery’s needs to using market penetration strategy for business competition. Market penetration refers to a increase sell promotion through online advertising, product publicity from a various event and increase sales force to gain intensive selling in the penetration area. Keywords: Strategy, SWOT, Market Penetration